Faktor-Faktor Yang Berhubungan dengan Kurangnya Minat Ibu Dalam Menggunakan Kontrasepsi Implant di Wilayah Kerja Puskesmas Sukarami Kecamatan Sungai Rotan Kabupaten Muara Enim Tahun 2025 - Meni Anggrayani; Ratna Dewi; Eka Rahmawati (Universitas Respati Indonesia, 2026)
Implant contraception is one of the effective methods to prevent pregnancy; however, its utilization in society remains low. According to LKRI data in 2023, implants ranked third with a percentage of 6.2%. In the working area of Sukarami Public Health Center, Sungai Rotan Sub-district, Muara Enim Regency, the number of implant acceptors was only 5.3% in 2024 and decreased to 2.7% in early 2025, which is lower compared to other contraceptive methods. This study aims to determine the relationship between knowledge, parity, and husband’s support with the use of implant contraception in the working area of Sukarami Public Health Center, Sungai Rotan Sub-district, Muara Enim Regency in 2025. The research design employed was an analytic survey with a cross-sectional approach. The study population consisted of all active family planning participants at Sukarami Public Health Center, Sungai Rotan Sub-district, Muara Enim Regency, with a total sample of 82 respondents selected using accidental sampling. The research instrument was a structured questionnaire to measure variables of knowledge, parity, husband’s support, and the use of implant contraception. Data analysis was conducted univariately and bivariately using the Chi-Square test. The results showed a significant relationship between knowledge (p=0.000), parity (p=0.002), and husband’s support (p=0.002) with the use of implant contraception. The conclusion of this study is that knowledge, parity, and husband’s support play an important role in determining women’s interest in using implant contraception.